2014
DOI: 10.1016/j.celrep.2014.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Tumor Subpopulations Cooperate to Drive Invasion

Abstract: SummaryClonal selection and transcriptional reprogramming (e.g., epithelial-mesenchymal transition or phenotype switching) are the predominant theories thought to underlie tumor progression. However, a “division of labor” leading to cooperation among tumor-cell subpopulations could be an additional catalyst of progression. Using a zebrafish-melanoma xenograft model, we found that in a heterogeneous setting, inherently invasive cells, which possess protease activity and deposit extracellular matrix (ECM), co-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
179
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(191 citation statements)
references
References 34 publications
7
179
1
2
Order By: Relevance
“…5(a)-(d) show a travelling pulse behaviour exhibited by the u 2 population that moves away from population u 1 (which is mostly stationary -although even this population spreads a bit). This faster spreading of the u 2 cells compared to the u 1 cells is consistent with experimental observations (Chapman et al, 2014;Wojciechowska & Patton, 2015). The movement of u 2 population eventually stops near the boundary (due to the periodic boundary conditions, the leftmoving and right-moving subgroups can sense each other across the boundary).…”
Section: Numerical Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…5(a)-(d) show a travelling pulse behaviour exhibited by the u 2 population that moves away from population u 1 (which is mostly stationary -although even this population spreads a bit). This faster spreading of the u 2 cells compared to the u 1 cells is consistent with experimental observations (Chapman et al, 2014;Wojciechowska & Patton, 2015). The movement of u 2 population eventually stops near the boundary (due to the periodic boundary conditions, the leftmoving and right-moving subgroups can sense each other across the boundary).…”
Section: Numerical Resultssupporting
confidence: 76%
“…DYNAMICS OF CANCER CELLS. Experimental studies (Chapman et al, 2014) have shown that cancer cells can switch from a homogeneous type of invasion to a heterogeneous type of invasion described by invading chains (Chapman et al, 2014;Friedl & Wolf, 2003;Wojciechowska & Patton, 2015). Here, we assume that u 1 cells can mutate into u 2 cells at a constant rate M. We can derive a model for heterogeneous cancer cell populations by considering the equations…”
Section: Derivation Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of cooperation has been further characterized in other models proposing a leading invasive cell followed by "opportunistic" cells ( Fig. 5B; Chapman et al 2014;Westcott et al 2015). This synergy is in agreement with the observation that CTC clusters have dramatically increased metastatic potential compared with single CTCs (Aceto et al 2014) and the polyclonal nature of metastases (Gundem et al 2015;Maddipati and Stanger 2015).…”
Section: Clonal Cooperationsupporting
confidence: 72%
“…Cancer cells can switch from a homogeneous type of invasion to a heterogeneous type of invasion described by (directionally moving) invading chains. 12 Therefore, we assume that the movement of the early stage cancer cell population u 1 is governed by random motility (which underlines a homogeneous type of invasion), as well as directed motility in response to cell-cell and cell-matrix adhesive forces (which underlines the heterogeneous type of invasion).…”
Section: The Mathematical Model Of Tgf-β Regulatorymentioning
confidence: 99%